Error In Oral Production By English Department Students Of Muhammadiyah University Of Surakarta - Ilmiani, Dwi, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M.Pd (2014)
This study deals with error in oral production made by english department students of Muhammadiyah University of Surakarta. The aims of this study are (1) to classify the type of errors, (2) to analyze the frequency of error utterances in oral production, (3) to analyze the dominant type of error, and (4) to describe the sources of error in speaking showed up by English department students of UMS. The type of this research is descriptive qualitative research. The data source of this research is error utterances that made by English department students in psycholinguistic presentation class. The data collection technique is documentation. The technique of data analysis is descriptive. The writer uses the theories from Clark and Clark, James and Selinker to analyze the type of error. The result of this study shows that (1) the writer found four types of error namely: speech error, pronunciation error, grammatical error, and code switching; (2) The frequency of each type of error are 139 utterances of speech errror (74,33%), 33 utterances of pronunciation error (17,67%), 8 utterances of grammatical error (4,27%), 7 utterances containing code switching (3,74%); (3) the dominant types of error is speech error especially filled pause; there are 53 utterances filled pause or about 28,34%; (4) the sources of error are cognitive reason, psychological reason, socials reason, the interlingual transfer and intralingual transfer. In interlingual transfer there are four categories, namely language interference, transfer in grammar, pronunciation interference, transfer in vocabulary. In itralingual transfer, there are two categories, namely false analogy and incomplete rule application.